Intermetallics 2016 - Ana Sofia Ramos (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The combination of low density, high strength, and good corrosion resistance makes intermetallics promising for structural applications, especially at high temperatures and under severe environments. These materials have also potential for functional applications since some intermetallic phases have unique properties, such as shape memory or thermo electric effect. As a result of the increasing demand for novel/advanced materials with improved properties, recent years have been marked by the return of intermetallics. In this book, 17 papers have been published covering important aspects related to intermetallics, in particular transition metal aluminides. Other materials, such as silicides, NiTi shape memory alloys and Ti-6Al-4V, were also investigated. Composites involving intermetallics were the subject of two papers, while two papers were dedicated to metallic glasses. Processing and joining of intermetallics, their mechanical properties and oxidation/corrosion behaviour, phase transformations involving intermetallics, modelling and numerical simulation have been focused on these papers. The simulation and experimental works carried out allowed understanding the relation between microstructure and properties of the intermetallics studied, aiming at their use as structural materials at high and ultra-high temperatures, as well as in aerospace/aeronautic, automobile, electronic, tribological, and biomedical applications. Whatever the application, joining of intermetallics to other materials is of paramount importance as is reflected in this book that contains several papers dedicated to this topic.